2018
DOI: 10.1186/s40560-018-0326-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcomes of early post-operative veno-arterial extracorporeal membrane oxygenation following infant cardiac surgery

Abstract: BackgroundWe aimed to determine predictors of, and outcomes after, veno-arterial extracorporeal membrane oxygenation instituted within 48 h after cardiac surgery (early ECMO) in young infants.MethodsPatients ≤ 6 weeks old having cardiac surgery from 2003 to 2012 were enrolled prospectively. Patients cannulated pre-operatively, intra-operatively, or ≥ 48 h post-operatively were excluded. Variables at p ≤ 0.1 on univariate regression were entered into multiple logistic regression to predict early ECMO. Early-ECM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Consistent with previous reports ( 13 , 27 , 28 ), we have shown the primary cardiac defect of single ventricle and the peri-operative risk factor of CPR are important determinants of mortality. While GA and body weight did not predict death, the intra-uterine growth of the fetus as reflected by low birthweight z- scores was critical for this prediction.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous reports ( 13 , 27 , 28 ), we have shown the primary cardiac defect of single ventricle and the peri-operative risk factor of CPR are important determinants of mortality. While GA and body weight did not predict death, the intra-uterine growth of the fetus as reflected by low birthweight z- scores was critical for this prediction.…”
Section: Discussionsupporting
confidence: 93%
“…13 A high-peak inotropic score predicted mechanical support in children requiring ECMO support, following fulminant myocarditis. 14,15 In our study, we found that while on ECMO, decreasing trend of vasoactive inotropic score over the first 5 days was associated with successful weaning and significantly improved survival on VA-ECMO (p value 0.003).…”
Section: Discussionmentioning
confidence: 54%
“…If accompanied with serious complications, ECMO could not successfully wean off in shorand long-term assist devices, or switch to left ventricular assist device as bridge to heart transplantation should be considered. 16 In this group, there were eight patients with assist time of 1 to 3 days and five survived, nine patients assisted for 3 to 5 days and seven patients discharged; however, six patients assisted for more than 5 days and all died (p ¼ 0.01). Our results were close to the ELSO statistics, indicating that ECMO duration was one of the main factors affecting survival.…”
Section: Ecmo Durationmentioning
confidence: 82%